Systems Pharmacology Based Strategy for Q-Markers Discovery of HuangQin Decoction to Attenuate Intestinal Damage - Dai, Xiao-min; Cui, Dong-ni; Wang, Jing; Zhang, Wei; Zhang, Zun-jian; Xu, Feng-guo (Frontiers in Pharmacology, 2018)
The quality control research of traditional Chinese medicine (TCM) is lagged far behind the space of progress in modernization and globalization. Thus the concept of quality marker (Q-marker) was proposed recently to guide the quality investigations of TCM. However how to discover and validate the Q-marker is still a challenge. In this paper, a systems pharmacology based strategy was proposed to discover Q-marker of HuangQin Decoction (HQD) to attenuate Intestinal Damage. Using this strategy, 9 measurable compounds including paeoniflorin, baicalin, scutellarein, liquiritigenin, norwogonin, baicalein, glycyrrhizic acid, wogonin and oroxylin A were screened out as potential markers. Standard references of these 9 compounds were pooled together as components combination according to their corresponding concentration in HQD. The bioactive equivalence between components combination and HQD was validated using wound healing test and inflammatory factor determination experiment. The comprehensive results indicated that components combination is almost bioactive equivalent to HQD and could serve as the Q-markers. In conclusion, our study put forward a promising tool for Q-markers discovery.